270 MONOCLONAL GAMMOPATHY FOLLOWING CORD BLOOD TRANSPLANTATION FOR CHEDIAK-HIGASHI SYNDROME. Issue 1 (1st January 2007) - Wang, K. Y.S.; Lin, E. M.; Roberts, R. L.
Abstract : Introduction: Chediak-Higashi syndrome (CHS) is a rare autosomal recessive disorder that often undergoes progression to a life-threatening accelerated phase with lymphohistiocytic infiltration in multiple organs. We report a case of CHS in the accelerated phase that was successfully treated with IVIG and high-dose corticosteroids. He then went underwent cord blood transplantation that was successful, but he later developed a monoclonal gammopathy. Case Report: Our patient was diagnosed with CHS at 16 months of age by peripheral blood smear, which revealed giant granules in his white blood cells. His parents declined bone marrow transplantation at that time. He was placed on G-CSF for his associated neutropenia. At 6 years of age, he presented to us with pancytopenia, fever, respiratory stress, mental status changes, and seizure activity. On physical examination, he had significant hepatosplenomegaly. Laboratory studies revealed hemoglobin 10.0 g/dL, platelets 34 × 10(9)/L, and leukocytes 1.3 × 10(9)/L. Parvovirus PCR was positive. Bone marrow biopsy showed cytoplasmic inclusions granule and hemophagocytic cells. Head MRI showed nonspecific focal hyperintensity in the subcortical white matter, consistent with lymphohistiocytic infiltration. For treatment, he received three courses of IVIG (4.5 g/kg total). He was also given methlyprednisolone 30 mg/kg/d × 3 days, followed by 20 mg/kg/d × 4 days and then 10 mg/kg/d × 3 days. He was then placed on dexamethasone 0.4 g/kg/d × 1 month, followed by 0.3 mg/mg/d × 1 month and then maintenance for 0.1 mg/kg/d until the time of transplantation. He underwent splenectomy due to persistent thrombocytopenia. Over the course of several weeks, his mental status returned to baseline, seizure activity ceased, hepatomegaly resolved, and pancytopenia improved. Repeat bone marrow biopsy showed rare hemophagocytic cells, and repeat head MRI showed significant improvement. Therefore, his accelerated phase had undergone remission. He then received a 10/10 match cord blood transplantation. RFLP showed 30% donor chimerism with 70% recipient cell lineage. The patient appeared to engraft successfully following the transplantation and routine infusions of IVIG were stopped. Approximately 15 months after transplantation, the patient was clinically stable, but serum IgG level was found to be 4000 mg/dL and his CD 4/8 ratio was 0.55. Immunoelectrophoresis revealed that he had developed a monoclonal IgG gammopathy. Bone marrow and repeat RFLP studies are being done to further investigate this abnormality.